Myeloid Heme Oxygenase-1 Regulates the Acute Inflammatory Response to Zymosan in the Mouse Air Pouch. (11th February 2018) - Brines, Rita; Catalán, Laura; Alcaraz, Maria José; Ferrándiz, Maria Luisa
Abstract : Heme oxygenase-1 (HO-1) is induced by many stimuli to modulate the activation and function of different cell types during innate immune responses. Although HO-1 has shown anti-inflammatory effects in different systems, there are few data on the contribution of myeloid HO-1 and its role in inflammatory processes is not well understood. To address this point, we have used HO-1 M-KO mice with myeloid-restricted deletion of HO-1 to specifically investigate its influence on the acute inflammatory response to zymosan in vivo . In the mouse air pouch model, we have shown an exacerbated inflammation in HO-1 M-KO mice with increased neutrophil infiltration accompanied by high levels of inflammatory mediators such as interleukin-1 β, tumor necrosis factor- α, and prostaglandin E2 . The expression of the degradative enzyme matrix metalloproteinase-3 (MMP-3) was also enhanced. In addition, we observed higher levels of serum MMP-3 in HO-1 M-KO mice compared with control mice, suggesting the presence of systemic inflammation. Altogether, these findings demonstrate that myeloid HO-1 plays an anti-inflammatory role in the acute response to zymosan in vivo and suggest the interest of this target to regulate inflammatory processes.